UMPSA received a visit from Fort De Kock University, Indonesia - Nor Salwana, Mohammad Idris (UMPSA, 2024)
GAMBANG, 23 July 2024 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) recently welcomed a delegation from Fort De Kock University, Indonesia, to its Gambang Campus.